2020
DOI: 10.1002/jcp.29820
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of TRPM7 enhances TRAIL‐induced apoptosis in triple‐negative breast cancer cells

Abstract: Transient receptor potential cation channel subfamily M member 7 (TRPM7) composed of an ion channel and a kinase domain regulates triple‐negative breast cancer (TNBC) cell migration, invasion, and metastasis, but it does not modulate TNBC proliferation. However, previous studies have shown that the combination treatment of nonselective TRPM7 channel inhibitors (2‐aminoethoxydiphenyl borate and Gd3+) with tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) increases antiproliferative effects and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) can selectively induce apoptosis in various types of cancer cells. Song et al [ 124 ] investigated whether TRPM7 knockdown or pharmacological inhibition of the channel can enhance TRAIL-induced apoptosis in triple-negative breast cancer cells (MDA-MB-231 and MDA-MB-468). Among other findings, the authors demonstrated that pharmacological inhibition of the channel or kinase units in TRPM7 using NS8593 and TG100-115, respectively, synergistically increases TRAIL-induced apoptosis in breast cancer cells [ 124 ].…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) can selectively induce apoptosis in various types of cancer cells. Song et al [ 124 ] investigated whether TRPM7 knockdown or pharmacological inhibition of the channel can enhance TRAIL-induced apoptosis in triple-negative breast cancer cells (MDA-MB-231 and MDA-MB-468). Among other findings, the authors demonstrated that pharmacological inhibition of the channel or kinase units in TRPM7 using NS8593 and TG100-115, respectively, synergistically increases TRAIL-induced apoptosis in breast cancer cells [ 124 ].…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…Several studies have illustrated the role of glutamate receptor in the pathophysiology mechanisms underlying multiple cancers, including breast cancer, glioblastoma, squamous cell lung cancer, prostate cancer, bladder cancer and melanoma [30][31][32][33][34][35]. Besides, researches have demonstrated the critical role of cation channels in the progression of various type of cancer, especially transient receptor potential cation channel subfamily V member 4 (TRPV4) [36-38], transient receptor potential cation channel subfamily M member 7/8 (TRPM7/8) [39][40][41][42] and two-pore channel 2 (TPC2) [43,44]. TPC2 is one of the cation channels located on endolysosomal membranes that could speed up movement between organelles and regulate phagocytosis, autophagy and lysosomal exocytosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Another nonselective cation channel TRPM7 involved in Ca 2+ and Mg 2+ homeostasis mainteinance has been found to manage cell differentiation, proliferation and migration. TRPM7 suppression in triple-negative breast cancer (TNBC) cells could amplify tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced antiproliferation and apoptosis [42]. In PAAD, TRPM7 was higher expressed in tumor tissues compared to the normal and correlated to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in other breast cancer cells, MDA-MB-231, inhibition of the channel with NS8593, increases the apoptotic and antiproliferative effects induced by TRAIL, while inhibition of kinase activity with TG100-115 has no effect, suggesting that TRPM7 mediates TRAIL-induced apoptosis via calcium ion fluxes [ 109 ]. In addition, downregulation of the activities of the TRPM7 channel could regulate a reduction in the level of c-FLIP L protein promoting the activation of caspase-8, improving apoptosis and decreasing the expression of c-FLIP S .…”
Section: Role Of Trpm7 In Breast Cancer Pathophysiologymentioning
confidence: 99%